Differential ultrasonic calorimeter for accurate measurement of thermal losses in machinery - Hashmi, Anas (2017)
Ultrasonic sensors can rapidly respond to changes in the average temperature across a complete ultrasonic pathway. However, these response rates are difficult to achieve using conventional temperature-sensing technologies. This research investigates ultrasound calorimetry and its advantages over the calorimetry implemented using conventional temperature sensors in order to estimate heat losses accurately in electrical motors. The ultrasonic calorimeter is based upon ultrasonic oscillating temperature sensors, which have previously been demonstrated in temperatures that change only in a single direction.